2009
DOI: 10.1093/hmg/ddp074
|View full text |Cite
|
Sign up to set email alerts
|

In vitro supplementation with dAMP/dGMP leads to partial restoration of mtDNA levels in mitochondrial depletion syndromes

Abstract: Mitochondrial DNA depletion syndrome, a frequent cause of childhood (hepato)encephalomyopathies, is defined as a reduction of mitochondrial DNA copy number related to nuclear DNA. It was previously shown that mtDNA depletion can be prevented by dAMP/dGMP supplementation in deoxyguanosine kinase-deficient fibroblasts. We investigated myotubes of patients diagnosed with mtDNA depletion carrying pathogenic mutations in DGUOK, POLG1 (Alpers syndrome) and TYMP. Differentiating myotubes of all patients and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 43 publications
1
60
1
Order By: Relevance
“…This decrease in mtDNA copy number is consistent with the mtDNA deficiency that was shown in patient samples from muscle tissue. Supplementation with dAMP and dGMP now causes a significant 250% increase in mtDNA copy number (paired t-test value of 0.035) also consistent with that previously published in DGUOK deficient myoblasts [21].…”
Section: Resultssupporting
confidence: 89%
“…This decrease in mtDNA copy number is consistent with the mtDNA deficiency that was shown in patient samples from muscle tissue. Supplementation with dAMP and dGMP now causes a significant 250% increase in mtDNA copy number (paired t-test value of 0.035) also consistent with that previously published in DGUOK deficient myoblasts [21].…”
Section: Resultssupporting
confidence: 89%
“…It has been reported that expression of a yeast mitochondrial repair/recombination enzyme, Cce1, the cruciform-cutting endonuclease, in human cells harboring partially duplicated mtDNA induced the appearance of wt mtDNA, thus demonstrating that expression of a yeast protein could be beneficial for mtDNA stability in mammalian cells [78]. Such a genetic rescue could be associated to a treatment with dNTPs, which seems to be beneficial for the detrimental effects caused by specific mutations in human POLG : the processivity defect of human DNA polymerase gamma harboring Y955C mutation was overcome by increasing the dATP or dTTP concentration during in vitro synthesis of mtDNA fragments [65] and the treatment with dAMP and dGMP leads to a slight increase in the levels of mtDNA in myoblasts deriving from an Alpers' patient harboring mutations A467T and K1191N in POLG [79].…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts from patients with TK2 deficiency, mitochondrial dTTP, dCTP, and dATP pools were all decreased while dGTP was slightly increased in one patient and slightly decreased in another patient [36]. The fact that externally supplied deoxyribonucleosides and deoxyribonucleoside monophosphates are able to rescue mtDNA depletion provides further evidence that limited substrate availability can cause mtDNA depletion [35, 37, 38]. Experiments from cellular and animal models have also reported disruptions in mitochondrial dNTP pool homeostasis [39-41].…”
Section: Introductionmentioning
confidence: 99%